2018
DOI: 10.1111/mec.14847
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling reveals deep‐sea coral response to the Deepwater Horizon oil spill

Abstract: Deep-sea coral communities are key components of the Gulf of Mexico ecosystem and were adversely affected by the Deepwater Horizon (DWH) oil spill. Coral colonies exposed to oil and dispersant exhibited mortality, damage and physiological signatures of stress. Understanding how corals respond to oil and dispersant exposure at the molecular level is important to elucidate the sublethal effects of the DWH disaster and reveal broader patterns of coral stress responses. Gene expression profiles from RNAseq data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 97 publications
0
32
0
Order By: Relevance
“…This survey was focused on healthy coral colonies throughout the northern Gulf, but also found a previously unknown coral community near Mississippi Canyon (MC294), which was visibly impacted by flocculent material containing both oil and dispersant (White et al, 2012(White et al, , 2014DeLeo et al, 2015). Visible impacts (e.g., mucous strands, loose tissue, and bare skeleton) from oiled flocculent material were assessed by examination of digital imagery for Paramuricea biscaya, Paragorgia regalis, and Swiftia pallida (White et al, 2012;DeLeo et al, 2018;Montagna and Girard, 2020). ROV surveys performed in 2011 as part of the NRDA (Fisher et al, 2014a,b) identified two additional coral sites (MC297, MC344) near (6-20 km) the DWH wellhead from 1,560 to 1,850 m water depth as also being visibly impacted by oiled flocculent material.…”
Section: Coralsmentioning
confidence: 99%
See 1 more Smart Citation
“…This survey was focused on healthy coral colonies throughout the northern Gulf, but also found a previously unknown coral community near Mississippi Canyon (MC294), which was visibly impacted by flocculent material containing both oil and dispersant (White et al, 2012(White et al, , 2014DeLeo et al, 2015). Visible impacts (e.g., mucous strands, loose tissue, and bare skeleton) from oiled flocculent material were assessed by examination of digital imagery for Paramuricea biscaya, Paragorgia regalis, and Swiftia pallida (White et al, 2012;DeLeo et al, 2018;Montagna and Girard, 2020). ROV surveys performed in 2011 as part of the NRDA (Fisher et al, 2014a,b) identified two additional coral sites (MC297, MC344) near (6-20 km) the DWH wellhead from 1,560 to 1,850 m water depth as also being visibly impacted by oiled flocculent material.…”
Section: Coralsmentioning
confidence: 99%
“…During the DWH (Figures 2B,F) MOSSFA and hydrocarbon intrusions ultimately caused an increase in particulate organic carbon flux ("marine snow"), advected detritus and dead falls as inputs to the benthic system (Paris et al, 2012;Valentine and Benfield, 2013;Romero et al, 2015;Lindo-Atichati et al, 2016). Certain microbial and chemotrophic communities' mineralization rates increased, lethal effects to meiofauna (specifically foraminifera) and sub-lethal effects to macrofauna, corals and megafauna were observed (White et al, 2012(White et al, , 2014Montagna et al, 2013;Valentine and Benfield, 2013;Mason et al, 2014;Schwing et al, 2015;DeLeo et al, 2018). Following DWH (1-2 years: Figures 2C,G), hydrocarbon toxicity remained elevated, surface sedimentary oxygen concentrations decreased, burial of petroleum carbon was initiated and unconsolidated flocculent material containing oil residue was re-suspended, causing changes in microbial, meiofaunal and macrofaunal community structure, and sub-lethal effects in corals and megafauna (Hsing et al, 2013;Montagna et al, 2013;Valentine and Benfield, 2013;Mason et al, 2014;Romero et al, 2015;Silva et al, 2015;Hastings et al, 2016;Yang et al, 2016;Schwing et al, 2017bSchwing et al, , 2018a.…”
Section: Conceptual Model Of Key Ecological Groups In Relation To Thementioning
confidence: 99%
“…Similar to the Turquoise and Black modules, genes within the Brown module were also downregulated in the highest nitrogen treatment and were enriched in functions relating to "DNA metabolic processes" and "DNA recombination" (Figure 5d). These been identified in deep-sea corals exposed to oil and dispersants (DeLeo et al, 2018).…”
Section: Functional Enrichment Of Modulesmentioning
confidence: 99%
“…The dendrogram shows the sharing of genes between categories and the fractions correspond to the number of genes significant within that category of genes. Individual genes from each GO term/module are detailed in Appendix S1 [Colour figure can be viewed at wileyonlinelibrary.com] in innate immunity have also been identified in corals(DeSalvo, Sunagawa, Voolstra, & Medina, 2010) and sponges(Guzman & Conaco, 2016) in response to increased temperature, as well as in oil-contaminated corals(DeLeo et al, 2018). Most notable, however, is a similar change in gene expression of immunity-related factors in Galaxea fascicularis from eutrophic environments(Lin et al, 2016).…”
mentioning
confidence: 99%
“…Each one of these habitats suffered from a loss of biodiversity caused by the smothering effects of oil as well as lethal and sublethal effects from a multitude of chemical compounds contained in crude oil [13]. In addition, the use of industrial oil dispersants, such as Corexit A9500 1 , increased the bioavailability of the oil [14] and introduced synergistic toxic effects to some of the organisms [15,16,17].…”
Section: Introductionmentioning
confidence: 99%